A well-appearing infant with a sudden anisocoria. Issue 2 (6th October 2020) - Servidio, Alessia Giuseppina; Peri, Francesca; Tenore, Andrew; Cesca, Laura; Diplotti, Laura; Dall'Amico, Roberto; Barbi, Egidio
Abstract : Case presentation: A 10-month-old boy was admitted to the emergency department due to a sudden onset of left unilateral mydriasis (figure 1 ). His medical history was unremarkable. A minor head trauma 2 days before was reported, without alarming signs or symptoms. His mother was putting him to sleep, after coming back from work, when she noticed a different pupil size and promptly went to the ED with her husband. The parents denied any use of medications, including nebulised therapy or direct contact with plants. The child was well appearing and his vital signs were within the standard age limits. His extraocular motility was normal as well as the rest of his neurological and physical examination. Parents' behaviour was somehow remarkable. Even though the child was not suffering, the mother seemed very worried while the father was nervous and aggressive, repeatedly asking for a discharge. : Questions: What is the most likely diagnosis based on this clinical presentation? Local contact with a mydriatic substance Intracerebral haemorrhage Brain tumour Third nerve palsy What would be the next step in the investigation to confirm this diagnosis? Brain CT Brain MRI Fundus oculi examination Toxicological screening of urine How is this condition managed, and what is the prognosis? Answers can be found on page XX